Comparison of the Accuracy of Anterior Segment Optical Coherence Tomography and Ultrasound Biomicroscopy in Localizing Rectus Muscle Insertions. Issue 2 (3rd April 2022) - Mirmohammadsadeghi, Arash; Hamzeh, Nikoo; Ghassemi, Fariba; Akbari, Mohammad Reza
ABSTRACT: Purpose: To compare the accuracy of anterior segment optical coherence tomography (AS-OCT) and ultrasound biomicroscopy (UBM) in localizing rectus muscle insertions. Methods: The study was performed on 27 patients (39 rectus muscles) who required primary or secondary surgery. Using caliper function in the AS-OCT and UBM software, the distance from the insertion site to the anterior chamber angle was measured. The actual muscle insertion distance from limbus was considered as the measured distance plus 1 mm. The measurements by UBM and AS-OCT were compared with intraoperative measurements and with each other. Results: AS-OCT and UBM were performed on 13 medial rectus, 24 lateral rectus, and 2 superior rectus muscles. Ninety two percent of UBM measurements (36 muscles) were within 1 mm, one was within 1–1.5 mm, and 2 were within 1.5–2 mm of surgery measurements. Eighty five percent of AS-OCT measurements (33 muscles) were within 1 mm, 5 were within 1–1.5 mm, and one was within 1.5–2 mm of surgery measurements. In all cases, the mean absolute error of the UBM (0.54 ± 0.44) and AS-OCT (0.51 ± 0.36) showed no significant difference (p = .76). Conclusion: AS-OCT and UBM can be used interchangeably to localize rectus muscle insertions and showed good agreement with intraoperative measurements.